2006
DOI: 10.1016/j.ejcts.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire study investigating the prevalence of the neuropathic component of chronic pain after thoracic surgery

Abstract: Chronic pain has a significant prevalence and impact on patients' lives for several years after thoracic surgery. Nerve dysfunction is associated with more severe pain, a greater impact and tends to persist. The reason for the individual consultant being an important factor in post-thoracotomy pain needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
136
3
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(160 citation statements)
references
References 17 publications
7
136
3
14
Order By: Relevance
“…In previous studies, postoperative pain was reported between 0.8 and 93 % for thoracoscopic surgeries [2,10,11,13,[17][18][19]. Pain at the time of discharge affected 20 % of the patients, which decreased to 10 % at the tenth day of postoperation in our study.…”
Section: Discussionsupporting
confidence: 53%
“…In previous studies, postoperative pain was reported between 0.8 and 93 % for thoracoscopic surgeries [2,10,11,13,[17][18][19]. Pain at the time of discharge affected 20 % of the patients, which decreased to 10 % at the tenth day of postoperation in our study.…”
Section: Discussionsupporting
confidence: 53%
“…The most consistent finding in the literature thus far has been that the presence of current pain (either preoperative or acute postsurgical pain) predicts future pain [4,[9][10][11][12]. Other factors such as younger age [3,14], female gender [9,15], the presence of anxiety [9,16], pain catastrophizing [17], and other psychological variables such as emotional numbing [18] have been shown to predict the development ofpostsurgical pain after a variety of surgical procedures [4]. We must continue efforts to determine which aspects of the perioperative pain experience are predictive of the transition to pain chronicity: qualities specific to the pain itself (e.g.…”
Section: Introductionmentioning
confidence: 54%
“…Studies have reported that female gender [9] and younger age [9,40) predicted intense acute postoperative pain, and nationwide surveys consistently find that the incidence of chronic neuropathic pain is significantly higher in women than men [4143]. Several smaller studies of CPSP have also identified younger age as a risk factor for the transition from acute pain to pain chronicity [14,22]. The sample of patients enrolled in the present study was quite homogeneous with respect to age and gender and neither predicted chronic pain 6 months after total hip arthroplasty [19].…”
Section: Introductionmentioning
confidence: 99%
“…They found that the incidence of chronic pain 6 to 42 months after thoracotomy was 40% for thoracotomy and 47% for VATS. Likewise, Maguire et al (12) conducted a study of 948 cases of thoracotomy and postoperative chronic pain was observed in 57% of cases within 7-12 months of the surgery, in 36% of cases within 4-5 years of the surgery, and in 21% of cases within 6-7 years of surgery. In our study, we defined the incidence of chronic pain in the 1st month after thoracotomy as 20% for Group C, 15% for Group S, 10% for Group P, and 20% overall.…”
Section: Discussionmentioning
confidence: 99%